2021
DOI: 10.1039/d1tc03436g
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the surface space charge layer on undoped SrTiO3(001)

Abstract: SrTiO3, an ABO3-type perovskite structure, has been a popular choice of substrate for many important heterostructures, e.g., ferroelectric thin films and superlattices. As numerous exotic physical phenomena are closely related...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
(89 reference statements)
3
6
0
Order By: Relevance
“…43 In the case of the high-temperature annealing step, there is a high chance of surface segregation of Sr, which can form C(6 × 2) with SrO layer. 45,46 Based on the observation of the sharp (1 × 1) LEED patterns in Figure 1, we are confident that the surface is TiO 2 -enriched, as confirmed by previous reports. 38,39,43 There is also a possibility of having a stable OH-enriched surface when oxygen vacancies are created in a UHV chamber.…”
Section: Resultssupporting
confidence: 88%
“…43 In the case of the high-temperature annealing step, there is a high chance of surface segregation of Sr, which can form C(6 × 2) with SrO layer. 45,46 Based on the observation of the sharp (1 × 1) LEED patterns in Figure 1, we are confident that the surface is TiO 2 -enriched, as confirmed by previous reports. 38,39,43 There is also a possibility of having a stable OH-enriched surface when oxygen vacancies are created in a UHV chamber.…”
Section: Resultssupporting
confidence: 88%
“…This broader component is attributed to other chemical states of Sr that can form as a result of Sr excess near the surface of the film. Such Sr enrichment has been observed in many perovskite oxides 51 and can result from segregation of Sr-rich phases to the surface; 52 these could be SrO precipitates, as was shown, for example, in strontium titanate-based perovskites [53][54][55][56][57] and in SVO. 43 In other cases, the formation of surface Sr-rich Ruddlesden-Popper (RP) phases 58 has been reported in different perovskite oxides 19,59 and in SVO films, where structures of Sr 3 V 2 O 8 60,61 were identified.…”
Section: Resultsmentioning
confidence: 69%
“…6 indicates that our initial surface state of SrTiO 3 is consistent with the results of many other groups in the literature. 10,22,25 However, it is also important to notice that the impurities of Si and Al atoms still exist on the well-ordered SrTiO 3 surface. In many cases, SrTiO 3 serves as a substrate for other materials and the clean and controlled interfacial layer between the substrate and the overlayer is critical to the success of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…21 It is reported that the SrO surface layers are made by subsurface Sr vacancies, resulting in the formation of an electron depletion layer at the surface and the creation of upward band bending of the SrTiO 3 surface. 22,23 In the meantime, in order to promote the rather poor conductivity of the SrTiO 3 surface, the implantation of doping has been applied, especially to meet the need of photocatalyst research. C. Courter et al demonstrated that the reactivity of water dissociation on the SrTiO 3 surface was significantly enhanced with the increase of Nb dopant concentration due to the higher conduction electron density.…”
Section: Introductionmentioning
confidence: 99%